FINANCIAL SUSTAINABILITY INTHE ASSESSMENT OF THEFINANCIAL PERFORMANCE OF WEST SUMATRA SHARIA FINANCING BANK (BPRS) - Nasfi, Nasfi; Iska, Syukri; Nofrivul, Nofrivul; Antoni, Antoni (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2019)
The objective of research to examine the financial performance of the Bank Financing of Islamic People of West Sumatra. Data analysis techniques using the BPRS health assessment applicable in accordance with the decision of Bank Indonesia No. 9/17/PBI/2007 dated December 4, 2007, the financial aspects of the form CAR, FDR, NPF, ROA and BOPO. Results of the study found that the ratio of CAR, BPRS West Sumatera amounting to 14.27%, with "very healthy" assessment criteria, the ratio of FDR BPRS 75.67% of West Sumatra, with the assessment of "healthy" criteria, the ratio of NPF BPRS West Sumatra average 7.83%, the assessment "Quite Healthy" criteria, the ratio ROA BPRS West Sumatra an average of 1.34%, with "healthy" with the assessment criteria and the ratio of BOPO BPRS West Sumatera on average by 92.43%, with "very healthy" assessment criteria. The implications of this research to analyze the performance of the financial aspect of the BPRS can provide information about the circumstances and financial position of the company within a certain period in order to take a decision in the future moreover sharia financing bank should increase efficiency and lower the financing problem.Keywords: Financial performance, CAR, FDR, NPF, ROA and BOPO